Workforce ageing in europe – is the proces reaching all economic sectors to the same extent? - Szukalski, Piotr (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
Population ageing is closely related to workforce ageing, i.e. increase in percentage of people in the so called immobile working age (45-64) between all working age population. The process is observed in all UE countries, however is reaching in different manner particular economic sectors. The differentiation is related to such factors as stage of life cycle of the sector, who is owner (public vs. private), requirements towards workers on vitality, strength, or speediness of reaction. The paper is aimed at determining which UE economic sectors are the most "touched" be workforce ageing. The sectors will require a specific preparation to consequences of the workforce ageing – mass workers withdrawal from the labour market in a relatively short period and mass recruitment.